Effects of land use on the concentration and emission of nitrous oxide in nitrogen-enriched rivers. (July 2018) - Yang, Libiao; Lei, Kun
Abstract: Nitrous oxide (N2 O) is a potent greenhouse gas that contributes to climate change and stratospheric ozone destruction. Nitrogen-enriched rivers are significant sources of atmospheric N2 O. This study conducted a one-year field campaign in seven N-enriched rivers draining urban, rural, and agricultural land to determine the link between the production, concentrations, and emissions of N2 O and land use. Estimated N2 O fluxes varied between 1.30 and 1164.38 μg N2 O-N m −2 h −1 with a mean value of 154.90 μg N2 O-N m −2 h −1, indicating that rivers were the net sources of atmospheric N2 O. Concentrations of N2 O ranged between 0.23 and 29.21 μg N2 O-N L −1 with an overall mean value of 3.81 μg N2 O-N L −1 . Concentrations of ammonium and nitrate in urban and rural rivers were high in the cold season. The concentrations were also high in agricultural rivers in the wet season. N2 O concentrations and emissions in rural and urban rivers followed a similar pattern to ammonium and a similar pattern to nitrate in agricultural rivers. A strong link between the concentrations and emissions of N2 O and land use was observed. N2 O concentrations in and emissions from the rivers draining the urban and rural areas were significantly higher than the rivers draining the agricultural areas ( P < 0.01). Stepwise regression analysis indicated that dissolved N2 O were primarily influenced by NH4 + in agricultural rivers and by NO3 − in rural rivers; while dissolved N2 O in urban rivers was primarily predicted by temperature and reflected the integrated impact of sewage input and river hydrology. Nitrate-N and NO 3- -O isotope data and linear regression of N2 O and river water variables strongly indicated that dissolved N2 O was mainly derived from nitrification in agricultural rivers and denitrification in rural and urban rivers. Graphical abstract: Image 1 Highlights: Urban and rural rivers were hot spots for N2 O emission. N2 O concentrations in urban and rural rivers were high in cold seasons. Land use has great effect on riverine N2 O concentration and emission. N2 O concentrations in agricultural and rural rivers were controlled by NH4 + and DO.